Development and evaluation of a recombinant monoclonal human antibody with virus-neutralizing activity against the F glycoprotein of respiratory syncytial virus - Sergey A. Klotchenko; Ekaterina A. Romanovskaya-Romanko; Marina A. Plotnikova; Anastasia A. Pulkina; Aram A. Shaldzhyan; Dmitry S. Balabashin; Victoria A. Toporova; Teimur K. Aliev; Natalia E. Gyulikhandanova; Dmitry A. Lioznov (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Respiratory syncytial virus (RSV) is the most common pathogen causing lower respiratory tract infections in children. RSV also poses a serious threat to the elderly and immunocompromised patients. Developing a therapy based on recombinant human antibodies to block the RSV fusion (F) glycoprotein is urgent to reduce the incidence of RSV infections and prevent associated complications.